فن حدیث میں شیخ البانیؒ کے افکار کا تاریخی و تنقیدی جائزہ - ڈاکٹر ابرار محی الدین مرزا; ڈاکٹر ابرار محی الدین مرزا (FIKR-O NAZAR فکر ونظر, 2011)
Right from the period of the Holy Prophet (PBUH) the companions did not accept every Hadith immediately with as reported by the narrator without its examination on the baisis of strict principles of investigation and criticism of Hadith. Thus the tendencies of the venerable and highly esteemed companions during their period became formal and regular principles for the people to follow. During the period of Tabain the established principles of the companions were fully adopted and followed. During the time of Khilafat-e-Rashida, there was mutiny of martyrdom of Hazarat Usman (R.A) a trouble that provided temptation of forgery of Hadith under the cover of the former. It was obligation of the Ummah to cope with this temptation. Since the Muslim Ummah dealt with it with a strong hand, therefore the art of tradition of Hadith was more elevated. If Imam Zuhri and his supporters were eminent in Madinah to cope with this temptation, then Imam Ibrahim Nakhee and his pupils were prominent in Kufa. After discussing the role played by those well known people the tendencies of Imam Abu Hanifa (d. 150h); Imam Malik (d. 179h). Imam Muhammad (d. 189h); Imam Shafiee (d. 204h); Imam Abdul Razzaq Ibn-el-Hamam (d. 211h); Imam Ibn-e-Abi Shaiba (d. 235h); Imam Ahmad Bin Hanbal(d. 241h); Imam Ibn-e-Hazm (d. 465h) and Allama Shokani (d. 1250h) have been discussed. The Disparity or contradiction of these capable scholars in derivation of hadith have also been discussed.